Podcasts As a Medium to Foster the Historical Imagination of Students During the Covid-19 Pandemic - Nur'aini, Fatwa; Supriatna, Nana; Ratmaningsih, Neiny (Paramita: Historical Studies Journal, 2023)
Online learning caused polemics in education, so teachers began showing action in creative pedagogy through the learning media, such as podcasts. This study aims to describe podcast media that can be used to grow students’ historical imagination in learning History and Social Sciences. Historical imagination is the cognitive ability to add or fill an insufficient space of historical facts. This research uses qualitative methods with a phenomenological approach. The subject of this study was an eleventh-grade student of the social studies program at SMA Negeri 1 Tuntang and a teacher—data collection through online interviews via a Google form. The results showed that podcast media is a form of creative learning in history and social studies. Podcasts as a medium to grow students’ historical imagination through the material “Stories from the Past” and “Come on Listen” content. The results showed that 74.6% of students responded positively about implementing podcast media. Despite having a high presentation in positive responses, 22.2% of students still have difficulty understanding the material using podcast media, and the rest feel ordinary, so they give advice. Based on this, it can be concluded that podcast media can be used to grow students’ historical imagination despite several internal and external obstacles. An internal bottleneck in the podcast creation process takes quite a while. In contrast, external barriers are caused by students’ growing demands for podcast-based learning.Keywords: Media Podcast, Historical Imagination, Social Studies, Covid-19 PandemicPembelajaran daring menimbulkan polemik dalam dunia pendidikan, sehingga guru mulai berunjuk aksi dalam pedagogi kreatif melalui media pembelajaran yang digunakan seperti pemanfaatan media podcast. Penelitian ini bertujuan untuk mendeskripsikan media podcast yang dapat digunakan untuk menumbuhkan historical imagination peserta didik dalam pembelajaran Sejarah dan Ilmu Pengetahuan Sosial selama pandemi covid-19. Historical imagination merupakan kemampuan kognitif untuk menambah atau mengisi ruang fakta sejarah yang tidak lengkap. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Subjek penelitian ini merupakan siswa kelas XI program IPS di SMA Negeri 1 Tuntang dan seorang guru. Pengambilan data melalui wawancara secara online melalui google form. Hasil penelitian menunjukkan bahwa media podcast sebagai bentuk pembelajaran kreatif dalam pembelajaran Sejarah dan IPS. Podcast sebagai media untuk menumbuhkan historical imagination peserta didik melalui konten materi, konten “Cerita dari Masa Lalu (CDML)”, dan konten “Come on Listen”. Hasil penelitian menunjukkan terdapat 74, 6% siswa memiliki respon positif tentang implementasi media podcast dalam pembelajaran. Walaupun memiliki presentasi yang cukup tinggi dalam respon positif, namun ada 22,2% siswa masih mengalami kesulitan memahami materi menggunakan media podcast, dan sisanya merasa biasa saja sehingga hanya memberikan saran. Berdasarkan hal tersebut, dapat disimpulkan bahwa media podcast dapat digunakan untuk menumbuhkan historical imagination peserta didik selama masa pandemi covid-19 walaupun memiliki beberapa hambatan, baik secara aspek internal maupun eksternal. Hambatan secara internal proses pembuatan podcast yang membutuhkan waktu cukup lama. Sementara hambatan secara eksternal disebabkan oleh tuntutan siswa yang semakin banyak tentang pembelajaran berbasis podcast.Kata Kunci: Media Podcast, Historical Imagination, IPS, Pandemi Covid-19